NONABLATIVE LASER TREATMENTS AS AN ALTERNATIVE TO ABLATIVE LASER PROCEDURE - Betyna, Monika; Zieliński, Ewa; Zieliński, Maciej; Motylewski, Bernard; Skalski, Dariusz; Brzoskowska, Karolina (Rehabilitation and Recreation, 2020)
Nowadays, we have various ways to check if new collagen was formed. One of such researches used this method to check effects of non-ablative laser treatments. Laser treatments have been one of the best methods of skin remodeling since they were introduced into aesthetic medicine and cosmetology. Numerous patients on the whole world benefit from this kind of face rejuvenation. However, lasers, when we speak about skin rejuvenation, have their bad effects. One of them is definitely healing process and the second one is possible damage to skin because of ablation. Recent techniques, non-ablative laser treatments, definitely take away the two drawbacks mentioned before - except skin ablation; there is less healing time and less probability of permanent damage to skin. However, is this enough to have also very good effects? Is it possible without proper damage to have very good results? This paper will investigate this matter on the basis of opinions of doctors and biophysics experts in the field of aesthetic medicine and cosmetology. All in all, the non-ablative laser devices, together with skin-cooling device, are proven to be safe and effective for skin rejuvenation in patients regardless their nationality. The advantages of such techniques for wrinkle reduction include the easiness of performance, lack of patient discomfort and treating all skin types without the high risk of epidermal injury. Non-ablative resurfacing techniques are very well suited for patients who need rejuvenation for their aging face. No matter what laser type is introduced, when speaking of non-ablative procedures, regardless of the fact if wrinkles, fine lines or skin surface is treated, the effects are subtle and gradual, comparing to ablative techniques, which are more aggressive. Various lasers are introduced to identify the best modality; however the extended pulse lasers are seen to provide particular benefits. Both the 1320nm and 1064nm lasers, when co-working with a skin-cooling device, are unique and appropriate for all skin types. Furthermore, these treatments are regarded as safe, and with less downtime for patients.